Phylogenetic studies of the subgenus Petrophilus Chaudoir (Coleoptera: Carabidae: Pterostichus), with description of a new species sympatric with P. thunbergi Morawitz - Sasakawa, Kôji; Kubota, Kôhei (Zootaxa, 2006)
Based on the structures of the male genitalia, the subgenus Petrophilus Chaudoir is redefined, and five subgenera, viz., Euryperis Motschulsky, Morphnosoma Lutshnik, Euferonia Casey, Feroperis Lafer, and Moritapterus Berlov, are synonymized with Petrophilus. Phylogenetic analyses based on eighteen morphological characters revealed that the subgenus Petrophilus is monophyletic, whereas most traditional subgenera synonymized with Petrophilus are non-monophyletic. Pterostichus (Petrophilus) tuberifer Sasakawa, sp. nov., a sympatric species with P. thunbergi Morawitz, is described from Japan.